2018
DOI: 10.7754/clin.lab.2017.170611
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and Lead in Women Who Miscarried

Abstract: Elevated Cd and Pb concentrations in the blood and placenta of pregnant women may be connected with the occurrence of miscarriage; therefore, the levels of these heavy metals should be monitored in women who plan pregnancy. It seems that determining the level of molar ratio between toxic metal and antioxidant elements can be analyzed as a marker for selection for control examinations as a valuable complement to existing diagnostic procedures in prevention, especially in early pregnancy. Additional diagnostic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Lead's damage to the child can begin as early as pregnancy. Maternal lead can be passed through the placenta to the developing fetus [11,22]. The Pb content in the placenta is the result of many complex biochemical reactions and various factors related to the mother's body.…”
Section: Location Of Lead In the Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Lead's damage to the child can begin as early as pregnancy. Maternal lead can be passed through the placenta to the developing fetus [11,22]. The Pb content in the placenta is the result of many complex biochemical reactions and various factors related to the mother's body.…”
Section: Location Of Lead In the Bodymentioning
confidence: 99%
“…The susceptibility of the developing fetus to lead's adverse effects and the potential for preventing additional postnatal lead exposure justify intervention for pregnant women showing signs of exposure to lead [22]. When mothers blood lead concentrations are high, they should be encouraged to pump and eject milk until the level of lead in the blood drops below 40 μg/dl [23].…”
Section: Prevention and Monitoring Of Lead Poisoningmentioning
confidence: 99%
“…Animal studies have shown that toxic metals accumulate in selected organs and pass through the placental barrier to the fetus, causing teratogenic and embryotoxic effects in a wide variety of species . However, the evidence of metal toxicity in human embryos is deficient …”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] There are numerous reports on the effects of these toxic metals on human health, especially during the gestation period of pregnant women. [33][34][35] Human TIP1 is involved in various signaling pathways controlling key biological processes including regulation of the cerebral concentration of neurotransmitter glutamate, β-catenin-mediated Wnt signaling, Rho-activator Rhotekin, and potassium channel Kir2.3 signaling pathway. 11,16,[24][25][26]36 Considering the importance of TIP1 for the well-being of a living cell, it is of great importance to investigate the effect of toxic metals on the structure of TIP1 and consequently on its function below levels that are currently allowed.…”
mentioning
confidence: 99%
“…30-32 There are numerous reports on the effects of these toxic metals on human health, especially during the gestation period of pregnant women. 33-35 Human TIP1 is involved in various signaling pathways controlling key biological processes including regulation of the cerebral concentration of neurotransmitter glutamate, β-catenin-mediated Wnt signaling, Rho-activator Rhotekin, and potassium channel Kir2.3 signaling pathway. 11,16,24-26,36…”
mentioning
confidence: 99%